Process Optimization and Quality Evaluation of Pomegranate Juice Yogurt Fermented with Streptococcus thermophilus FUA329 - Yichen HUANG; Ziyan HUA; Gewen ZHANG; Shu LIU; Xiaoyue HOU; Kexin CHI; Guang YANG; Xiang ZHOU; Yaowei FANG (Shipin gongye ke-ji)
Metabolizing ellagic acid (EA) to urolithin A with numerous bioactivities significantly improve the nutritional value of food rich in EA. In the present study, Streptococcus thermophilus FUA329 was applied to prepare pomegranate juice yogurt. The best process formula was investigated through single-factor experiments and response surface methodology. With S. thermophilus CGMCC1.8748 as control, the viability of strain, rheological properties and antioxidant activity of pomegranate juice yogurt fermented with strain FUA329 were evaluated. The content of urolithin A in pomegranate juice yogurt fermented with strain FUA329 were analyzed by high-performance liquid chromatography. The results showed that the optimal fermentation conditions for preparing pomegranate juice yogurt by S. thermophilus FUA329 were 15.79% pomegranate juice content, 7.08% sucrose content and 3.04% starter inoculum size, fermentation at 37 ℃ for 7 h and comprehensive sensory score was 79.4 points. Under the optimal conditions, the results of basic indicators showed that yogurt acidity was (82.5±1.3)°T, whey precipitation was 9.6%±0.97%, color difference was 68.17±2.75, bacterial activity was 2.01±0.31 (OD600). In terms of antioxidant activity, DPPH radical, ABTS+ radical and superoxide anion radical scavenging rates of fermented pomegranate juice yogurt by strain FUA329 were 82.87%±1.48%, 88.20%±2.10% and 76.92%±1.02%, respectively, which was significantly better than plain yogurt fermented by strain FUA329 and pomegranate juice yogurt fermented by S. thermophilus CGMCC1.8748. In addition, urolithin A content was 3.31 μmol/L in fermented pomegranate juice yogurt by strain FUA329 after 7 h. The results of this study would provide a theoretical basis for fermenting a functional pomegranate juice yogurt, and lay a foundation for the development and utilization of S. thermophilus FUA329.